A digitizing craftsmanship: a comparative study of traditional vs. SDF-based shoe last making using 3D scanning and computer numerical control technologies - Surya, G.; P., Anbarasan; Suresh, B. (Frontiers in Mechanical Engineering, 2025)
IntroductionThis study compares traditional and advanced shoe last manufacturing processes, emphasizing the integration of 3D scanning and the SDF (Sistema Definizione Forma) system to improve efficiency and precision.MethodsIn the traditional method, physical models are manually sculpted and digitized using mechanical digitizers. These are then machined via CNC systems, requiring manual finishing—particularly in toe and heel areas—due to clamping limitations. Branding is completed using conventional heat embossing tools. In contrast, the advanced method employs digital modeling tools (e.g., Rhino software) to directly create shoe last designs. These digital files are processed in SDF-enabled CNC machines, utilizing a dovetail gripping mechanism that allows full-surface precision turning and eliminates the need for manual finishing. Logos and markings are applied using laser printing.ResultsThe SDF-based approach demonstrated over 70% improvement in production speed, an 80% reduction in manual intervention, and sub-millimetric dimensional accuracy. Surface finish, repeatability, and suitability for mass customization were also significantly enhanced.DiscussionFindings support that the SDF-based method enables a more sustainable, scalable, and higher-quality production process compared to traditional methods, offering clear advantages for modern footwear manufacturing.